2014
DOI: 10.1111/gcb.12618
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus additions impact arbuscular mycorrhizal abundance and molecular diversity in a tropical montane forest

Abstract: Increased nitrogen (N) depositions expected in the future endanger the diversity and stability of ecosystems primarily limited by N, but also often co-limited by other nutrients like phosphorus (P). In this context a nutrient manipulation experiment (NUMEX) was set up in a tropical montane rainforest in southern Ecuador, an area identified as biodiversity hotspot. We examined impacts of elevated N and P availability on arbuscular mycorrhizal fungi (AMF), a group of obligate biotrophic plant symbionts with an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
135
4
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 202 publications
(171 citation statements)
references
References 159 publications
(350 reference statements)
16
135
4
8
Order By: Relevance
“…This approach yielded an estimate of 34 AMF taxa detected in roots on the basis of SSU-DGGE banding that has been shown, via individual band sub-cloning and sequencing, to underestimate AMF diversity (Öpik et al 2003), although it assumes we did not have any nonspecific amplification from other fungal phyla (see Kohout et al 2014). The clearest relationship between soil nutrients and AMF taxa representation was seen for soil N. A related study in species rich tropical montane forest found reduced AMF species richness in bulked root samples in response to N and P addition (Camenzind et al 2014). Nitrogen input in forests will be greatly dependent on anthropogenic deposition rates but also associative and symbiotic Nfixation involving legumes.…”
Section: Discussionmentioning
confidence: 81%
“…This approach yielded an estimate of 34 AMF taxa detected in roots on the basis of SSU-DGGE banding that has been shown, via individual band sub-cloning and sequencing, to underestimate AMF diversity (Öpik et al 2003), although it assumes we did not have any nonspecific amplification from other fungal phyla (see Kohout et al 2014). The clearest relationship between soil nutrients and AMF taxa representation was seen for soil N. A related study in species rich tropical montane forest found reduced AMF species richness in bulked root samples in response to N and P addition (Camenzind et al 2014). Nitrogen input in forests will be greatly dependent on anthropogenic deposition rates but also associative and symbiotic Nfixation involving legumes.…”
Section: Discussionmentioning
confidence: 81%
“…Total concentrations of P, Ca, Al, Fe, K, Mg, and Zn as well as soil pH were analyzed on separate soil samples taken in February 2013 (important elements which were included in this study were preselected by principal component analysis, selecting for ecologically relevant variables and excluding collinear predictors Camenzind et al, 2014). Samples were obtained from all six subplots (taken with a soil corer of 3.5 cm diameter), pooled separately for each plot and transferred to University of Tübingen and Freie Universität Berlin for further analyses.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…However, tropical forests are highly endangered by deforestation, land use change, fertilization but also increased nutrient deposition by anthropogenic activities (Gullison et al, 2007;Galloway et al, 2008;Mahowald et al, 2008). Increases in nutrient deposition have been shown to affect plant diversity, ecosystem productivity, soil community composition as well as nutrient cycling (Treseder, 2008;Bobbink et al, 2010;Isbell et al, 2013;Wilcke et al, 2013b;Camenzind et al, 2014), and thus also directly or indirectly may have an impact on soil aggregation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Mycorrhizae live in close symbiosis with plants and their responses to nutrient addition depend partially upon plant nutrient status as well as background nutrient limitation (Treseder, 2004). N deposition decreases arbuscular mycorrhizal biomass in both temperate and tropical forests (Johnson et al, 2003;Treseder, 2004;Camenzind et al, 2014;Krashevska et al, 2014;Wurzburger and Wright, 2015), but responses to N and P addition are context-dependent. Ecological relationships between plants and their mycorrhizae depend both upon soil C:N:P stoichiometry (Johnson et al, 2015) and mycorrhizal type (e.g., arbuscular, ectomycorrhizal, etc).…”
Section: Figure 1 | Conceptual Model Of How Nitrogen Addition Affectsmentioning
confidence: 99%